"Dissociation, posttraumatic stress symptoms, emotional dysregulation, and invalidating environments as correlates of NSSI in borderline personality disorder patients". Issue 5 (19th October 2020) - Perez, Sandra; Lorca, Fátima; Marco, Jose H.
ABSTRACT: Theoretical models have proposed that inadequate caregiving environments undermine the development of adaptive regulation strategies at early stages and can lead children to inadequate regulation skills for coping with distress, such as dissociation, posttraumatic stress, and NSSI. The main aim of this work was to examine NSSI types and functions and the relationship between the aforementioned variables and lifetime NSSI in 102 patients with BPD diagnoses or BPD subthreshold symptoms. In addition, we explored the moderator role of dissociation between invalidating environments and NSSI. Results showed that 83.7% of the sample self-injured more than 5 times during their lifetime; 62.7% swallowed dangerous substances; 58.8% hit themselves; and 46% cut themselves. Regression analyses revealed that the model including variables with significant correlations with NSSI explained 27% of the variance in NSSI, with dissociation and invalidating behaviors of the father best explaining the variance in NSSI. In addition, dissociation moderated the association between invalidating behaviors of the father and NSSI. These results highlight the important role of invalidating environments, dissociation, and posttraumatic stress symptoms in NSSI in patients with BPD, and the need to assess and treat dissociation and posttraumatic symptoms in this population.